Preferences for health care and self-management among Dutch adolescents with chronic conditions: A Q-methodological investigation - Jedeloo, S.; van Staa, A.; Latour, Jos; van Exel, N. (Elsevier Ltd, 2010)
Background: Adolescents with chronic conditions have to learn to self-manage their health in preparation for transitioning to adult care. Nurses often struggle with how to approach youth with chronic conditions successfully. Little is known about the preferences and attitudes of these young people themselves. Objective: To uncover preferences for self-management and hospital care of adolescents with various chronic conditions. Design and method: A Q-methodological study was conducted. Semi-structured interviews were held with adolescents who rank-ordered 37 opinion statements on preferences for care delivery and self-management. They were asked to motivate their ranking. By-person factor analysis was conducted to uncover patterns in the rankings of statements. The factors were described as preference profiles. Participants and setting: A purposive sample of 66 adolescents (12-19 years) treated in a university children's hospital in the Netherlands was invited to participate. Thirty-one adolescents, 16 boys and 15 girls with various chronic conditions eventually participated (response 47%). Eight participants (26%) had a recently acquired chronic condition, while the rest (74%) had been diagnosed at birth or in the first 5 years of life. Results: Four distinct preference profiles for health care delivery and self-management were identified: 'Conscious & Compliant'; 'Backseat Patient'; 'Self-confident & Autonomous'; and 'Worried & Insecure'. Profiles differ in the level of independence, involvement with self-management, adherence to therapeutic regimen, and appreciation of the parents' and health care providers' role. The desire to participate in treatment-related decisions is important to all preference profiles. The profiles are recognizable to adolescents and nurses alike. As Q-methodology allows no inferences with respect to the relative distribution of these profiles in a given population, only tentative hypotheses were formulated about associations between profiles and patient characteristics. Conclusion: This study increases our understanding of different subjectivities of adolescents living with a chronic condition related to their treatment and health. There is no "one size fits all" approach to adolescent health care, but rather a limited number of distinct preference profiles. This study demonstrates the value of a non-disease-specific approach in that adolescents with various chronic conditions were found to have much in common. The profiles seem a promising tool for nurses to actively seek adolescents' opinion and participation in health care and will be further explored. © 2009 Elsevier Ltd. All rights reserved.